Optimasi Parameter Tekanan Deposisi untuk Penumbuhan Lapisan Tipis Mikrokristal Silikon dengan Metode HWC PECVD - Amiruddin Supu; I Wayan Sukarjita; Fakhruddin Fakhruddin; Fitri Suryani Arsyad; Toto Winata; Sukirno Sukirno (Jurnal Matematika & Sains, 2008)
The Hot Wire Cell PECVD method has been developed and successfully applied to grow the hydrogenated microcrystalline silicon ( Âµc-Si:H) thin films. The Âµc-Si:H thin films were grown on the 7059 corning glass at a filament temperature of 1000 oC. Ten percents silane (SiH4) gas diluted in hydrogen (H2) gas was used as gas source. In the hot wire cell PECVD method, reactant gases are decomposed as a result of reaction with a heated filament. The filament was placed parallelly with inlet gas system and outside of electrodes. The characterization results exhibited that the deposition rate increased from 1,45 Ã/s to 1,56 Ã/s with increasing the deposition pressure from 700 mTorr to 1100 mTorr. The SEM image and the XRD spectrum exhibited the transition of amorphous to microcrystalline silicon at an deposition pressure of 1000 mTorr. The transition of amorphous to microcrystalline was indicated by the reduction of amorphous parts and the appearance of peak diffraction at preferential crystal orientation. The dark and photo conductivities of the obtained Âµc-Si:H thin films was 1,2 x10-5 S cm-1 and 2,12 x 10-3 S cm-1, respectively.